Limiting the Excess Broadcast in Multipath Routing Using Ant Colony Optimization - Kaur, Amanpreet; Singh, Gurpreet; Gupta, Rohan (International Journal of Engineering and Technology, 2018)
Single path routing in mobile adhoc network (MANET) suffers from frequent disconnections due to movement of nodes. So, multipath routing evolves as a solution to the single path routing. Many researchers are working on devising multipath routing protocols with new features and strategies. Ant colony optimization is also used by many investigators for developing new solutions for multipath routing in MANET. In this paper we have worked on controlling the broadcast being done by the intermediate nodes. We improved on our work done in Amanpreet Kaur et al. titled â€œACO Agent Based Routing in AOMDV Environmentâ€ by making use of channel contention and backoff technique. We compared the newly designed algorithm with three broad categories unipath, multipath and ant based algorithm. The new algorithm performs better as compared with other algorithms on the basis of various QoS metrics like throughput, jitter, end to end delay, and number of packets send, lost in packets and delivery ratio. Â Â